Public sector performance measurement practice in Malaysia - Abdullah, Nur Anisah (2013)
Performance measurement is becoming more relevant as the government is pressuring for more efficient and effective service delivery. A series of in-depth exploratory face-to-face interviews were conducted with public managers of 19 agencies and public bodies across the country asking them to share their experience with what works with performance measurement. Verbatim transcripts of the interviews were thematically coded and analysed. Findings reveal that in addition to the statutory requirement of external reporting, agencies measure performance for improvement. They demonstrate a level of interest in working towards improving how they measure performance, design measure and are progressing towards more effective use of performance information. Agencies were seen to be actively using KPIs to steer employee performance behaviour. There were signs of fatigue due to the laborious task of data collection and the lack of resources specifically allocated for performance measurement. Overall, performance measurement is pervasive across agencies and public bodies.